Mixed-use developments in the Philippines terminologies, determinants and development guidelines - Regunay, Catherine Joselle M. (School of Urban and Regional Planning, University of the Philippines Diliman, 2019)
The concept of mixed-use development (MXD) stems from the idea of sustainable communities where all activities and requirements of the population are situated in one place requiring little movement. Residential facilities, commercial centers, office spaces, leisure spaces, and service facilities are all located on single sites where everything people need is within short travel distance. This creates great opportunities for revenue generation, both for the private sector and government sector in the form of taxes and land values. In the Philippines, the urban landscapes has significantly transformed over the last decade as real estate developers are devoting a great deal of resources and attention to creating MXDs in primary cities. Planning for MXDs requires a strong relationship between the private sector (i.e. the developer) and the government sector. However, in the Philippines, there is a lack of interaction and collaboration between the two sectors brought about by insufficient information on this typology, in the absence of data and an operational definition of MXDs. This has resulted in inconsistent design and space programming, mixed land use zonings, and an illegible built up landscape. The study identified the nature and definition of MXD in the Philippines, their key determinants for location, and the preliminary guidelines that can be used in effectively creating mixed-use development and maximizing their features for the benefit of all users. By using three existing MXD in the Philippines as case studies, the study proposes an operational definition of an MXD by looking at it from the perspective of both the private sector and the government sector. The definition and identification of parameters distinct from MXDs as defined in international literature provide further understanding of the typology. These also serve as the basis of formal guidelines for MXDs. Furthermore, the study proposes possible actions to be taken on how the private and government sector can be work together toward the goal of creating a growing sustainable built landscape.